Association between nurse turnover and missed nursing care in acute care hospitals in South Korea - Bae, Sung-Heui (Frontiers in Medicine, 2025)
ObjectivesHigh nurse turnover during nursing shortages can contribute to missed nursing care. This study investigated the prevalence of missed nursing care and how nurse turnover affects missed nursing care.MethodsA cross-sectional design was adopted to collect data from a convenience sample of nurses working in general hospitals in South Korea. Six-month turnover rates (0%, 1–14%, 15–22%, and 23–50%) and 24 missed nursing care activities were measured. A multivariate regression analysis was performed to examine the relationship between nurse turnover and missed nursing care, after controlling for nurse and work-related characteristics.ResultsThe final sample was 264 nurses. The mean six-month turnover rate was 15.49%. Seven activities (turning patient every 2 h, attending interdisciplinary care conference, ambulation, patient bathing/skin care, emotional support, mouth care, full documentation) had a missed care prevalence of 30% or higher. Nurses in units with moderate turnover rates (15 and 22%) reported more missed nursing care than those in units with zero turnover.ConclusionNurse turnover increases missed nursing care, highlighting the adverse effects of nurse turnover on care processes. Consequently, hospitals and governments should implement policy changes and strategies to prevent nurse turnover.